(3MOjbI GdCRgGQ aj TQM eGgjI GdYTH hGdYbGQs - (3bGSe Hf eMeO Hf EHQGgje GdhRjQ GdZSGfj, GdhRjQ,J (B1019 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdYdj GdQNGHj GdJj dG JHjf Hc jO GddEfaGbj s
(3BNQgG (B:s
(3TLQI GdRjJhf , hbO JbOe TQM eGgjJgG hWHjYJgG hefGbHgG hNhGUgG hHOdgG ai HGH MQa GdRGj s
(3Vef eLehY , JQJjHgG (B: (3ef U (B117 - (3U(B224s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B182s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B82 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B- (3GdQHGW (B(71) s
Keywords: (3GdWHs